Associations between polycyclic aromatic hydrocarbon (PAH) exposure and oxidative stress in people living near e-waste recycling facilities in China. (September 2016) - Lu, Shao-you; Li, Yan-xi; Zhang, Jian-qing; Zhang, Tao; Liu, Gui-hua; Huang, Ming-zhi; Li, Xiao; Ruan, Ju-jun; Kannan, Kurunthachalam; Qiu, Rong-liang
Abstract: Emission of polycyclic aromatic hydrocarbons (PAHs) from e-waste recycling activities in China is known. However, little is known on the association between PAH exposure and oxidative damage to DNA and lipid content in people living near e-waste dismantling sites. In this study, ten hydroxylated polycyclic aromatic hydrocarbons (OH-PAHs) and two biomarkers [8-hydroxy-2′-deoxyguanosine (8-OHdG) and malondialdehyde (MDA)] of oxidative stress were investigated in urine samples collected from people living in and around e-waste dismantling facilities, and in reference population from rural and urban areas in China. The urinary levels of ∑10 OH-PAHs determined in e-waste recycling area (GM: 25.4 μg/g Cre) were significantly higher ( p < 0.05) than those found in both rural (11.7 μg/g Cre) and urban (10.9 μg/g Cre) reference areas. The occupationally exposed e-waste workers (36.6 μg/g Cre) showed significantly higher ( p < 0.01) urinary Σ10 OH-PAHs concentrations than non-occupationally exposed people (23.2 μg/g Cre) living in the e-waste recycling site. The differences in urinary Σ10 OH-PAHs levels between smokers (23.4 μg/g Cre) and non-smokers (24.7 μg/g Cre) were not significant ( p > 0.05) in e-waste dismantling sites, while these differences were significant ( p < 0.05) in rural and urban reference areas; this indicated that smoking is not associated with elevated levels of PAH exposure in e-waste dismantling site. Furthermore, we found that urinary concentrations of Σ10 OH-PAHs and individual OH-PAHs were significantly associated with elevated 8-OHdG, in samples collected from e-waste dismantling site; the levels of urinary 1-hydroxypyrene (1-PYR) ( r = 0.284, p < 0.01) was significantly positively associated with MDA. Our results indicate that the exposure to PAHs at the e-waste dismantling site may have an effect on oxidative damage to DNA among selected participants, but this needs to be validated in large studies. Graphical abstract: Highlight: Associations between PAH exposure and oxidative stress were explored in e-waste recycling area. E-waste recycling activities contribute to high human exposure to PAHs. Smoking is not an important contributor to PAH exposure in e-waste dismantling site. PAH exposure was associated with oxidative damage to DNA.